Friendships in childhood & adolescence - Bagwell, Catherine (Guilford series on social and emotional development., 2011)
"Highly readable and comprehensive, this volume explores the significance of friendship for social, emotional, and cognitive development from early childhood through adolescence. The authors trace how friendships change as children age and what specific functions these relationships play in promoting adjustment and well-being. Compelling topics include the effects of individual differences on friendship quality, ways in which certain friendships may promote negative outcomes, and cutting-edge research approaches. Examining what clinicians, educators, and parents can do to help children who struggle with making friends, the book reviews available interventions and identifies important directions for future work in the field."--